Communication Techniques Of Aquamarine Band In Delivering Messages During Performance On Stage - Akbar, Ahmad Faiq; Endang , Anis; Sari , Sapta (Multidisciplinary Journals, 2024)
There are many ways to deliver messages communicate, in directly or via media, either verbal or non verbal way. In order to make a messages received by other people obviously a communicator uses a communication technic, there are six communication technics that are known in Communication Studies such as Informative Technic, Persuasive Technic, Coersive Technic, Instructive Technic, Pervatie Technic, and Humanizm-Relationship Technic. And in this research, the author wanted to find out a kind of communication technic that was used by Aquamarine Band in delivering messages when performing on the stage, However, the technic wich was taken by author focused on three Communication technic only, they are an Informative Technic, Persuasive Technic, and Humanizm-Relationship Technic. In qualitative descriptive method, the author succeeded to observe that Aquamarine Band Absolutly uses those three Communication Technics as suitable as author’s research indeed, those are an Informative, Persuasive, and a Humanizm-Relationship Technic. This was proved from the result of the author’s interview with informers who consust of main informer, A Vocalist of Band and the head informer, that was Aquamarine Band fans club themsolves. They stated that every time when Aquamarine Band perform, they always interact to the crowd such as greeting, waving hands, encouraging all people to sing moreover, after performing there are always some people want to take a picture together